Effects of BTK signalling in pathogenic microorganism infections. Issue 10 (8th August 2019) - Ye, Bingjue; Zhou, Cheng; Guo, Huiting; Zheng, Min
Abstract: As a cytoplasmic protein tyrosine kinase, Bruton's tyrosine kinase (Btk) is widely considered as a vital kinase in many aspects of different physiologic processes. It is engaged in many important signalling pathways related to the immune response, such as the B cell receptor pathway, pattern‐recognition receptor pathway, and triggering receptor expressed on myeloid cell pathway. Recent studies have increasingly focused on the important role of Btk in various inflammatory diseases, which are related to Btk expression in myeloid innate immune cells, such as macrophages, dendritic cells and neutrophils. Although some investigations have explored the role of Btk in microbial infections, many aspects remain elusive, and some of the results are opposite and controversial. Considering the complicated and multiple roles of Btk in the immune system, we summarized the engagement of Btk signalling in various pathogenic microorganism infections, the possible mechanisms involved and its therapeutic potential in the control of infectious diseases.